Nutritional status and dietary adequacy in people living with HIV: a systematic review - Pragya Yadav; Meenakshi Khapre (International Journal Of Community Medicine And Public Health, 2026)
HIV infection adversely affects nutritional status by increasing metabolic demands, impairing nutrient absorption, and reducing dietary intake. Malnutrition and dietary inadequacy among people living with HIV (PLHIV) contribute to immune suppression, poor treatment response, and accelerated disease progression, yet nutrition remains an underemphasized component of HIV care. This systematic review aimed to assess the nutritional status and dietary adequacy of PLHIV by synthesizing evidence from Indian and international studies. A systematic literature search was conducted using PubMed, Google Scholar, and Scopus for studies published between 2010 and 2025. Observational and cross-sectional studies evaluating dietary intake, nutritional status, anthropometric parameters, dietary diversity, and related clinical outcomes among PLHIV were identified using predefined inclusion criteria and synthesized narratively following PRISMA reporting guidelines. Most studies reported inadequate energy and protein intake among PLHIV, with intakes frequently below recommended levels. Micronutrient deficiencies, anemia, and poor dietary diversity were common. Anthropometric findings revealed a dual burden of malnutrition, with both undernutrition and emerging overweight observed. Poor dietary diversity, food insecurity, and socioeconomic factors were consistently associated with adverse nutritional and clinical outcomes. PLHIV remain vulnerable to nutritional inadequacy and malnutrition, with energy and protein intakes consistently below recommended levels and dietary diversity scores below five food groups in most populations studied. Both undernutrition and emerging overweight represent a dual burden requiring individualized assessment. Integrating structured nutritional screening, counselling, and food supplementation into routine HIV care programs is essential to improve immunological recovery, reduce opportunistic infections, and enhance quality of life.